Personality Resources of Adolescents in the Educational Environment - Irina A. Baeva; Larisa A. Gayazova; Irina V. Kondakova (Economic History, 2021)
Introduction. The relevance of the study is determined by the importance of the category “psychological safety” for the support of the life quality of modern people, which is influenced in a complicated way by physical health, psychological well-being, value preferences, features of social relations and their relation to the characteristic features of the environment. The state of psychological safety is a significant factor ensuring the effectiveness of еducation, upbrining and development of the younger generation. However, the personal resources that contribute to the support of this state among adolescents and young people in the educational environment are more understudied. The purpose of the article is to determine the resources of adolescents, which are the predictors of the state of psychological safety. Materials and Methods. The method “Psychological safety of the educational environmentˮ developed by I.А. Baeva was used to study students’ level of psychological safety. The method of S. Schwartz was used to assess the personality’s value orientations, to assess the level of psychological well-being – were used Ryff Scales of Psychological Well-Being (RPWB), the level of loneliness – UCLA Loneliness Scale (D. Russell, M. Ferguson), the level of hopelessness – Hopelessness Scale, Beck et al., the level of social intelligence – Tromsø Social Intelligence Scale, the level of aggression – Buss-Perry Aggression Questionnaire, hardiness – Hardiness Survey (S. Maddi). The methods of mathematical statistics used in the research (descriptive statistics, correlation and regression analyzes) are implemented by means of the IBM SPSS Statistics 19 package. Results. It has been proven that the resources of adolescents’ psychological safety in the educational environment are: values, psychological well-being, social intelligence, hardiness and a low level of aggressiveness. The state of psychological safety is influenced by such manifestations as conformity and following traditions, a positive image of the future, ...